Cyclic Peptoid-Peptide Hybrids as Versatile Molecular Transporters - Herlan, Claudine Nicole; Meschkov, Anna; Schepers, Ute; Bräse, Stefan (Frontiers in Chemistry, 2021)
Addressing intracellular targets is a challenging task that requires potent molecular transporters capable to deliver various cargos. Herein, we report the synthesis of hydrophobic macrocycles composed of both amino acids and peptoid monomers. The cyclic tetramers and hexamers were assembled in a modular approach using solid as well as solution phase techniques. To monitor their intracellular localization, the macrocycles were attached to the fluorophore rhodamine B. Most molecular transporters were efficiently internalized by HeLa cells and revealed a specific accumulation in mitochondria without the need for cationic charges. The data will serve as a starting point for the design of further cyclic peptoid-peptide hybrids presenting a new class of highly efficient, versatile molecular transporters.